Hambatan Pemenuhan Hak Restitusi bagi Anak Penyandang Disabilitas sebagai Korban Kekerasan Seksual : Studi Putusan Nomor:323/Pid.Sus/2023/Pn.Skt - Reza Aulia Qusnul Khotimah (Pemuliaan Keadilan, 2025)
A child who becomes a victim of a criminal act, often referred to as a child victim, is one who experiences physical, psychological suffering, and/or loss of property due to a criminal act. In the case of children who are victims of sexual violence, it is not limited to physically healthy children, but also includes children with disabilities, whether physical, mental, or intellectual. These child victims have the right to restitution, which is a form of compensation for the harm and losses they have suffered. This study aims to identify the challenges faced by child victims of sexual violence and explain how the restitution process can be implemented within the context of Indonesian law. The author applies a normative research method and gathers data through literature review. The data obtained comes from legal regulations, court rulings, books, and relevant internet sources. The findings of this study indicate that restitution is a right granted to victims as a form of accountability from the perpetrator for their actions. Restitution aims to provide compensation for the victim’s suffering and loss, both materially and psychologically. However, several obstacles to fulfilling the right to restitution for child victims were identified. One of the main obstacles is the lack of understanding from the victim's family regarding the importance of restitution. Often, the victim’s family is unaware that they have the right to request restitution as part of the legal process. Additionally, inadequate cooperation between law enforcement and related institutions is another barrier to fulfilling the right to restitution. The lack of coordination between agencies in handling child sexual violence cases leads to delays in the restitution process. Therefore, it is crucial to raise awareness among the families of victims and improve cooperation between law enforcement, child protection agencies, and other related parties to ensure that the right to restitution is properly fulfilled.